Placing children and adolescents at the centre of the Sustainable Development Goals will deliver for current and future generations. Issue 1 (1st January 2019) - Alfvén, Tobias; Dahlstrand, Johan; Humphreys, David; Helldén, Daniel; Hammarstrand, Sofia; Hollander, Anna-Clara; Målqvist, Mats; Nejat, Sahar; Jørgensen, Peter Søgaard; Friberg, Peter; Tomson, Göran
ABSTRACT: Child health is taking the back seat in development strategies. In summarising a newly released collaborative report, this paper calls for a novel conceptual model where child health takes centre stage in relation to the 2030 Agenda and the Sustainable Development Goals. It lays out five principles by which renewed effort and focus would yield the most benefit for children and adolescents. These include: re-defining global child health in the post-2015 era by placing children and adolescents at the centre of the Sustainable Development Goals; striving for equity; realising the rights of the child to thrive throughout the life-course; facilitating evidence informed policy-making and implementation; and capitalising on interlinkages within the SDGs to galvanise multisectoral action. These five principles offer models that together have the potential of improving design, return and quality of global child health programs while re-energising the 2030 Agenda and the Sustainable Development Goals.